2017
DOI: 10.1002/iub.1627
|View full text |Cite
|
Sign up to set email alerts
|

Ketone bodies mimic the life span extending properties of caloric restriction

Abstract: The extension of life span by caloric restriction has been studied across species from yeast and Caenorhabditis elegans to primates. No generally accepted theory has been proposed to explain these observations. Here, we propose that the life span extension produced by caloric restriction can be duplicated by the metabolic changes induced by ketosis. From nematodes to mice, extension of life span results from decreased signaling through the insulin/insulin-like growth factor receptor signaling (IIS) pathway. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
119
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 143 publications
(123 citation statements)
references
References 87 publications
4
119
0
Order By: Relevance
“…[ 80 ] Ketone bodies were first discovered in the urine of diabetic patients and later found to increase in subjects undergoing starvation. [ 80 ] Lehninger and Greville showed that the βHB formed during ketosis was the d ‐isoform. Levels of this metabolite have been shown to increase to ≈2 × 10 −3 m in the fasting state or 0.6 × 10 −3 m during caloric restriction.…”
Section: Application Of Metabolomics For Biomarker Discovery In Agingmentioning
confidence: 99%
“…[ 80 ] Ketone bodies were first discovered in the urine of diabetic patients and later found to increase in subjects undergoing starvation. [ 80 ] Lehninger and Greville showed that the βHB formed during ketosis was the d ‐isoform. Levels of this metabolite have been shown to increase to ≈2 × 10 −3 m in the fasting state or 0.6 × 10 −3 m during caloric restriction.…”
Section: Application Of Metabolomics For Biomarker Discovery In Agingmentioning
confidence: 99%
“…Ketosis also increases forkhead box transcription factors (FOXO), which increase antioxidant enzymes and NAMPT expression . Increases in the tissue content of d ‐β‐hydroxybutyrate extend the life span of nematodes and possibly humans as well .…”
Section: The Measurement Of Coenzyme Couplesmentioning
confidence: 99%
“…content of D-β-hydroxybutyrate extend the life span of nematodes (21) and possibly humans as well (22).…”
Section: Variations In Total Cellular Nad Contentmentioning
confidence: 99%
“…In this sense, KBs increase the antioxidant power of these endogenous antioxidants (Kong et al, 2017;Veech et al, 2017). In this sense, KBs increase the antioxidant power of these endogenous antioxidants (Kong et al, 2017;Veech et al, 2017).…”
Section: K E Tone Bod Ie S (K Bs) and Amyotrophi C L Ater Al Scleromentioning
confidence: 96%